SWT and SIFT based copy-move image forgery detection - Das, Taposh; Azam, Md. Rasel; Hasan, Rizbanul (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.